RELIGIOUS UNDERSTANDING AND ISLAMIC GLOBALIZATION: HUMAN TRUTH FROM THE PERSPECTIVE OF ISLAM, A HISTORICAL REVIEW - Mohammad Sadiq Harifal; Enayatullah Dadman (CV. Radja Publika, 2024)
In an era marked by profound shifts in global dynamics, the intersection of religious understanding and Islamic globalization emerges as a critical locus of inquiry. This paper embarks on a nuanced exploration, delving into the depths of human truth as perceived through the complex prism of Islam. Anchored in a historical and political context, our analysis navigates through epochs of Islamic civilization, tracing the evolution of thought, belief systems, and the intricate interplay between religion and global dynamics. This research adopts a qualitative research design Qualitative methods such as textual analysis, historical review, and case studies are utilized to explore the religious understanding and Islamic globalization. the results of this research indicate that the discovery of religious understanding and Islamic globalization has a profound insight to find the human reality in Islamic tradition.